Padrões culturais avaliativos: um estudo sobre a adaptação de expatriados alemães no Brasil - Nakashima, Cleide (2013)
The presence of foreigners follows emerging economies, especially in Brazil where multinational companies grows on account of investments and business strategies. However, the production of knowledge about expatriation is still incipient and this research seeks to contribute to new reflections and discussions on the subject. The theme is broad and explored by several authors in Brazil and abroad for the international academics through various lenses ranging from intercultural issues to anthropological spheres. This research discusses the theory of Cultural Standards by Thomas (2010) with the overall objective of identifying the implications of Cultural Standards perceived by German expatriates to cultural adjustment in the Brazillian context. For this, categories of analysis were used concerning the transcultural adaptation of expatriates, proposed by Black and Stephens (1989). The work consisted of a qualitative research conducted by nine interviews, in which the reports were analysed and categorized. As a result, we identified ten German Cultural Standards about Brazilians involving the lack of fulfilment of promises agreed, the lack of systematic planning, lack of precision of information, informal and personalized relationships, apparent availability, bureaucratic processes, centralization of power and values such as cunning and the Brazilian jeitinho (way). The two main implications of these Cultural Standards found were the lack of trust and the feeling of the Germans of not being welcomed by the Brazilians.